Student’s Participation In Extracuricular School Sports Has Positive Impact On Executive Functions - Misbah Abdul Haris Nasution Alhanif; Purwo Sri Rejeki; Lilik Herawati (Universitas STRADA Indonesia, 2020)
The Audio and Visual Whole Body Reaction (WBR) motor function test uses the THP-15 tool, the balance test uses the Balance Error Scoring System (BESS), while the Working Memory (WM) executive function test uses the Forward Digit Span Task and the Inhibitory Control (IC) test using the Animal Stroop Task. The data analysis technique used the Pearson Chi-Square test with Statistical Package for Social Science (SPSS). The results obtained the mean of the visual Whole Body Reaction (WBR) motor function in the EO (0.55±0.21) and EBO (0.52±0.25) groups (p=0.558). The mean WBR Audio in the EO (0.73±0.24) and EBO (0.70±0.29) groups (p=0.918). The average balance in the EO group (1.65±0.54) and EBO (1.58±0.48) (p=0.297). Executive function of Working Memory (WM) in the EO (5.00±0.74) and EBO (5.19±0.74) groups (p=0.636). The mean inhibitory control (IC) in the EO group (4.61±2.09) and the EBO group (3.88±2.86) (p=0.048